2014
DOI: 10.1002/art.38675
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Anti‐Ro Antibody Exposure, Congenital Complete Atrioventricular Heart Block, and High‐Dose Steroid Therapy: Impact on Neurocognitive Outcome in School‐Age Children

Abstract: Objective. To determine the impact of prenatal exposure to maternal anti-Ro antibodies, slow fetal heart rate, and/or prolonged dexamethasone therapy for immune-mediated congenital atrioventricular heart block (CAVB) on the cognitive and academic performance of these children at school age.Methods. We performed a prospective, blinded assessment of the cognitive functioning of 3 cohorts of children ages 6-16 years with in utero exposure to maternal anti-Ro antibodies in the following groups: no CAVB and no pren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…In a recent review [95], only 7 neonatal lupus cases were identified as having a symptomatic CNS abnormality which caused physical disability or required neurosurgery. Moreover, the association of CHB and transplacental dexamethasone with neurocognitive impairment in school-age children was not confirmed in a recent study [96].…”
Section: Lupus Anti-ro/ssa and Anti-la/ssb Antibodies And Neonatal Lmentioning
confidence: 94%
“…In a recent review [95], only 7 neonatal lupus cases were identified as having a symptomatic CNS abnormality which caused physical disability or required neurosurgery. Moreover, the association of CHB and transplacental dexamethasone with neurocognitive impairment in school-age children was not confirmed in a recent study [96].…”
Section: Lupus Anti-ro/ssa and Anti-la/ssb Antibodies And Neonatal Lmentioning
confidence: 94%
“…Although data have been published suggesting that immune‐mediated AVB III can develop later in life, we are not aware of any report to date documenting that fetuses with delayed AV conduction have developed AVB III after birth. Importantly, even if smaller studies indicate that prenatal exposure to fluorinated steroids do not have negative effects on neuropsychological development or neurocognitive development, it is still a treatment with risk for adverse effects in both the mother and the fetus, and current data are not sufficient to specify the level of fetal AV conduction delay at which transplacental steroid treatment might be favorable for the fetus.…”
Section: Discussionmentioning
confidence: 95%
“…However, behavioural problems were present in both exposed and non-exposed children, with no statistical differences found among them. In a recent prospective study, Kelly et al 94 did not find neurocognitive impairment in school-age children exposed to maternal anti-Ro antibodies with or without CHB and did not find statistically differences in the intergroup comparison. The effect of prenatal corticosteroids on children's neurodevelopmental dysfunction has also been analysed in two studies 92,94 that found that prenatal exposure to dexamethasone, even at high doses, does not have negative effects on the neuropsychological/ neurocognitive development independently of having CHB or not.…”
Section: Late Complications In Children With Achbmentioning
confidence: 89%
“…[89][90][91] However, recent studies do not support these findings. [92][93][94] Brucato et al 92 did not find negative effects on the neuropsychological development in a small group of children exposed to maternal anti-Ro/SSA antibodies (with and without CHB). Askanase et al 93 reported a higher frequency of neuropsychiatric and neurodevelopmental dysfunction in anti-Ro/anti-La exposed children (regardless of their NL manifestations, including CHB), in comparison with healthy unexposed children.…”
Section: Late Complications In Children With Achbmentioning
confidence: 92%